Functional disorders and ‘medically unexplained physical symptoms’ - Price, J; Okai, D (Elsevier, 2016)
Functional disorders (FDs) are physical symptoms that trigger the sufferer to seek healthcare, but which remain unexplained after appropriate medical assessment. They are very common and cause significant distress and disability. Relevant aetiological factors can usually be discovered by careful and sympathetic clinical interview. What doctors say and do, and the way in which the healthcare system is organized, play a key role in aetiology. Although it is important to rule out serious physical pathology when patients present with physical symptoms, early ‘positive’ diagnosis of FDs can lead to better outcomes than diagnosis by exclusion. Commonly associated psychiatric conditions including depression, anxiety, substance abuse and personality disorders should be screened for. If reassurance and simple techniques of reattribution of symptoms do not lead to symptom resolution, cognitive behavioural therapy and the use of antidepressants as neuromodulating agents (rather than as antidepressants per se) should be considered.